Visual Sociology Practices and Politics in Contested Spaces - Zuev, D.; Bratchford, G. (2021)
This book provides a user-friendly guide to the expanding scope of visual sociology, through a discussion of a broad range of visual material, and reflections on how such material can be studied sociologically. The chapters draw on specific case-study examples that examine the complexity of the hyper-visual social world we live in, exploring three domains of the ‘relational image’: the urban, social media, and the aerial.